2006
DOI: 10.1002/micr.20208
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological follow‐up after splenectomy and spleen autotransplantation in mice

Abstract: We previously reported on a spleen autotransplantation model in mice, with spleen function studies at 6 weeks. The present study was undertaken to investigate long-term hemorheological functions. A/J and BALB/c inbred mice were divided into four groups: control, sham surgery (SH), splenectomy (SE), and spleen autotransplantation (AU). Hematological and hemorheological parameters were determined. Leukocyte counts in the SE and AU groups were significantly higher than in controls, while hematocrit levels were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…The median fibrinogen concentration in the HS patients with prior splenectomy (335 mg/dl) was at a level which has previously been associated with a twofold increased incidence of vascular events compared to subjects with fibrinogen level in the lowest tertile [41]. Elevated fibrinogen concentrations following splenectomy have previously been reported in mice [42], although other studies in human subjects have failed to show a significant difference in fibrinogen concentrations pre- and post-splenectomy in various conditions [43-45]. To our knowledge no prior studies have specifically examined patients with HS.…”
Section: Discussionmentioning
confidence: 99%
“…The median fibrinogen concentration in the HS patients with prior splenectomy (335 mg/dl) was at a level which has previously been associated with a twofold increased incidence of vascular events compared to subjects with fibrinogen level in the lowest tertile [41]. Elevated fibrinogen concentrations following splenectomy have previously been reported in mice [42], although other studies in human subjects have failed to show a significant difference in fibrinogen concentrations pre- and post-splenectomy in various conditions [43-45]. To our knowledge no prior studies have specifically examined patients with HS.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other studies have revealed that the presence of Howell-Jolly-bodies was clearly reduced with increased regeneration and splenosis rate of auto-transplantation splenic fragments (14,15). The OPSI is reported to be the most important and frequently fatal complication of total splenectomy.…”
Section: Discussionmentioning
confidence: 90%
“…spleen chips group could be related to the fact that not all of the spleen transplants were found in these experimental animals. They were supposedly in "functional hyposplenic state" at that time 17,26 . In the animal autotransplanted with 10 spleen chips the scintigraphy showed activity in the region of the greater omentum, confirming the phagocytic function of the autotransplants.…”
Section: Diagnostic Laparoscopymentioning
confidence: 99%